Pendampingan Mahasiswa Sebagai Agents of Change: Mendorong Penerapan Teknologi Informasi Yang Beretika dan Berlandaskan Nilai-Nilai Islam - Afriyanti, Liza; Iskandar, Iwan; Sandi, Wahyu Ari (Journal of Community Development, 2024)
The development of digital literacy is very important in facing the current digital era. In the educational context, digital literacy is the foundation that enables the learning process to be more interactive, dynamic and in line with current developments. This shows that digital literacy is not only relevant in everyday life, but also has a significant impact in the world of education, especially at the tertiary level. Students' digital literacy skills are an important aspect in facing the demands of today's digital era. However, just having information and communication technology skills is not enough, students are also required to understand, use and utilize digital technology effectively, responsibly and ethically with character and based on Islamic values. The form of service activity is a seminar which is held online via the zoom meeting application with the presentation method. To assess the achievement of goals and success of this service activity, the following indicators can be used as benchmarks, namely indicators of goal achievement and success benchmarks. By combining the two indicators above, it can provide a comprehensive picture of the achievement of objectives and the success of Community Service activities that have been carried out. Based on the evaluation results obtained from the reporting stage, it is known that this activity has various advantages and does not experience difficulties during its implementation, as well as assisting students as agents of change in the application of information technology can be carried out more ethically and based on Islamic values.